Polyketal Copolymers: A New Acid Sensitive Delivery Vehicle for Treating Acute Inflammatory Diseases - Yang, Stephen C. (2008)
Acute inflammatory diseases are a major cause of death in the world, and effective treatments are greatly needed. Macrophages play a central role in causing acute inflammatory diseases, and there is currently great interest in developing drug delivery vehicles that can target therapeutics to macrophages. Microparticles formulated from aliphatic polyketals have great potential to enhance the treatment of acute inflammatory diseases, due to their ability to passively target therapeutics to macrophages, their acid sensitivity, and their biocompatible degradation products. However, existing aliphatic polyketals are unsuitable for treating acute inflammatory diseases because they require weeks to hydrolyze, and strategies for accelerating their hydrolysis kinetics are greatly needed. In this report we demonstrate that the hydrolysis kinetics of aliphatic polyketals can be accelerated by increasing their hydrophilic/hydrophobic balance. Aliphatic polyketals of varying hydrophobicity were synthesized, via the acetal exchange reaction, and their hydrolysis kinetics were investigated at the pH values of 4.5 and 7.4. A polyketal termed PK3 was developed, which had the hydrolysis kinetics suitable for treating acute inflammatory diseases. PK3 has a hydrolysis half-life of 2 days at pH 4.5, but requires several weeks to hydrolyze at pH 7.4. Microparticles were formulated with PK3, which encapsulated the anti-inflammatory drug, imatinib. In vivo experiments demonstrated that PK3 microparticles were able to significantly improve the efficacy of imatinib in treating acute liver failure. We anticipate that aliphatic polyketals will have numerous applications for the treatment of acute inflammatory diseases, given their pH sensitivity, tunable hydrolysis kinetics, and biocompatible degradation products.